A process-oriented approach for documenting and gauging intercultural competence in translation. Issue 3 (1st September 2016) - Angelone, Erik
ABSTRACT: This article describes and contextualises how intercultural competence in translation can be empirically documented and assessed using a process-oriented dual methodology consisting of juxtaposed screen recording and think-aloud data. A discussion of how Byram's (1997) triadic intercultural communicative competence model of knowledge, skills and attitudes maps onto directly observable translator behaviours is followed by the results of a small-scale pilot study, which exemplify how various facets of intercultural competence are manifest in contexts involving MA-level student translation of German culturemes into US English. Continuing in the spirit of previous behaviour-oriented approaches to empirically document intercultural competence in translation, this article foregrounds process-oriented training as a means by which to glean insight into learner strengths and weaknesses with the objective of fostering growth in this domain, thereby optimising a still largely elusive area within translation pedagogy.